1987
DOI: 10.1002/j.2050-0416.1987.tb04495.x
|View full text |Cite
|
Sign up to set email alerts
|

The DEVELOPMENT OF Β-D-Glucanases DURING THE GERMINATION OF BARLEY AND THE EFFECT OF KILNING ON INDIVIDUAL ISOENZYMES†

Abstract: Two endo-1,3;1,4-p-D-glucanase isoenzymes developed in response to gibberellic acid, during the germination of barley. Two endo-1,3-p-D-glucanases, one present in ungerminated, steeped grain, also developed but did not appear to be markedly stimulated by the hormone. A comparison of crude and partially purified malt extracts highlighted the errors that are involved in the specific determination of endo-1,3;1,4-p-glucanase activity in crude extracts. The development and effect of kilning on individual malt isoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…These studies have shown that the initial activity of these enzymes is very low, but increases rapidly from the 2nd to the 4th day of the malting process. Nevertheless, the maximum values of enzyme activity ranged from the 4th, or 5th and 6th days, or even to the 11th day, in different experiments 1,3,14,20 . McFadden et al 17 verified that no mRNA encoding (1-3,1-4)-␤-glucanase is detected in ungerminated grain.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These studies have shown that the initial activity of these enzymes is very low, but increases rapidly from the 2nd to the 4th day of the malting process. Nevertheless, the maximum values of enzyme activity ranged from the 4th, or 5th and 6th days, or even to the 11th day, in different experiments 1,3,14,20 . McFadden et al 17 verified that no mRNA encoding (1-3,1-4)-␤-glucanase is detected in ungerminated grain.…”
Section: Discussionmentioning
confidence: 91%
“…Changes in the kilning temperatures and /or duration alter these results. Brunswick et al 3 kilned the malt at 60°C for 16 h, with resulting losses from 80 to 90% in (1-3,1-4)-␤-glucanase activity. Barber et al 2 , using a malting schedule with a more progressive temperature increase (from 30 to 65°C), observed a better survival of the (1-3,1-4)-␤-glucanase activity with losses from 16 to 26%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, ␣-amylase activity in most malting and feeding varieties is usually above the optimal level, at least when adjuncts are not required, so that differences above such a threshold have no effect on starch degradation during mashing 7 . Conversely, comparing activities of these enzymes in the kilned malt indicates a greater susceptibility of Extra enzymes to warm drying (stronger declines between 7 and 9 days), suggesting a diverse combination of differentially-thermostable isozymes was present 8 , which would justify the significance of the interaction effect (Table I). In regard to the effect of treatment, an initial higher temperature induced the higher ␤-glucanase activities, either integrated or in the green malt (Fig.…”
Section: Genotype × Treatmentmentioning
confidence: 99%
“…Furthermore, extraction of non-food products deposited in the endosperm of transgenic barley would be facilitated by the action of highly efficient, heat stable cell wall-degrading enzymes. The (1,3-1,4)-3-glucanases (EC 3.2.1.73) synthesized by the aleurone and scutellum tissues during barley grain germination (8) are susceptible to irreversible thermoinactivation at temperatures above 55°C (9,10), which may result in incomplete degradation of cell wall 13-glucans and limit the utility of barley for industrial processes unless a thermostable (1,3-1,4)-43-glucanase is present during extraction at elevated temperatures.…”
mentioning
confidence: 99%